2016
DOI: 10.1016/j.toxicon.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic effect of Dinoponera quadriceps giant ant venom

Abstract: Neglected tropical diseases (NTD) are treated with toxic therapy of limited efficacy. Previously, we studied the antimicrobial effect of Dinoponera quadriceps venom (DqV) against bacteria. To continue the study, we report in this short communication the antimicrobial effect of DqV against Leishmania amazonensis and Trypanosoma cruzi. DqV inhibits the promastigote forms of L. amazonensis and all T. cruzi developmental forms, with low toxicity in host cells. DqV causes cell death in T. cruzi through necrotic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Arthropod venoms are a rich, essentially untapped source for bioactive molecules. Among venomous insects, ants are remarkably chemically diverse 42 , as illustrated by a recent increase in the number of studies surveying the biomedical applications of ant toxins, such as the Brazilian giant ant Dinoponera quadriceps 43 . Among several other biomedical activities, the venom peptides of D. quadriceps were reported to be toxic to T. cruzi 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Arthropod venoms are a rich, essentially untapped source for bioactive molecules. Among venomous insects, ants are remarkably chemically diverse 42 , as illustrated by a recent increase in the number of studies surveying the biomedical applications of ant toxins, such as the Brazilian giant ant Dinoponera quadriceps 43 . Among several other biomedical activities, the venom peptides of D. quadriceps were reported to be toxic to T. cruzi 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating those data, Lima et al [ 67 ] reported the antimicrobial activity of the crude venom against methicillin-sensitive and resistant Staphylococcus aureus strains. The same researchers also reported the antiparasitic effects of the venom against Leishmania amazonensis and Trypanosoma cruzi [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h of incubation, the cells were washed to remove noninternalized parasites and treated with VIO (4·97 and 9·94 μmol l −1 ). The coverslips were collected in up to 24 and 48 h, washed with PBS, fixed in Bouin’s solution and stained with Giemsa (Lima et al ). Nontreated infected LLC‐MK2 cells were used as controls.…”
Section: Methodsmentioning
confidence: 99%